2020
DOI: 10.1021/acsami.9b23468
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Grain Growth in Organic–Inorganic Perovskite Films with Ethylamine Hydrochloride Additives for Highly Efficient Solar Cells

Abstract: The grain boundaries of perovskite polycrystalline are regarded as a defect region that not only provides carrier recombination sites but also introduces device degradation pathways. Efforts to enlarging the grain size of a perovskite film and reducing its grain boundary are crucial for highly efficient and stable perovskite solar cells (PSCs). Some effective methods that facilitate grain growth are postdeposition thermal annealing and solvent vapor annealing. However, a detailed understanding of grain growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…Additionally, a vast microstructure transformation was also enabled by the use of reduced-dimensionality perovskites or 2D/3D hybrid perovskites. [115,159,160] Figure 9c presents several kinds of molecules used to make 2D/3D hybrid perovskites. Among these, incorporating butylammonium iodide (BAI) into the caesiumformamidinium perovskite starting solution, the surface microstructure and crystal structures can vary when comparing the pristine 3D perovskite in Figure 9d, [148] with the formation of 2D/3D hybrid perovskites.…”
Section: Surface Catalyst For Microstructure Transformationmentioning
confidence: 99%
“…Additionally, a vast microstructure transformation was also enabled by the use of reduced-dimensionality perovskites or 2D/3D hybrid perovskites. [115,159,160] Figure 9c presents several kinds of molecules used to make 2D/3D hybrid perovskites. Among these, incorporating butylammonium iodide (BAI) into the caesiumformamidinium perovskite starting solution, the surface microstructure and crystal structures can vary when comparing the pristine 3D perovskite in Figure 9d, [148] with the formation of 2D/3D hybrid perovskites.…”
Section: Surface Catalyst For Microstructure Transformationmentioning
confidence: 99%
“…Previous calculations show that the surface energy of the (100) plane is the lowest in FA‐based perovskites. [ 23 ] Therefore, the crystal grains with the (100) plane parallel to the film surface grow preferentially during the annealing process. It is reported that the (100) surface has a lower defect density than the other planes in perovskite films.…”
Section: Resultsmentioning
confidence: 99%
“…As the defects associated with grain boundaries may induce losses, their volumetric fraction should be low compared to that of the ordered grains. As a consequence, the grain size is a crucial parameter, not only with conventional semiconductors like Si [9][10][11], but also with a number of currently emerging materials, such as halide perovskites [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%